Thiophene containing polycyclic aromatic hydrocarbon monkey saddles - Kirschbaum, Tobias; Daiber, Cornelius; Esteves, Joshua A.; Benke, Bahiru P.; Rominger, Frank; Elbert, Sven; Mastalerz, Michael (Asian journal of organic chemistry, 2025)
Negatively curved chiral polycyclic aromatic hydrocarbons (PAHs) have gained a significant amount of interest in recent years. By replacing the benzene moieties in a monkey saddle shaped PAH with thiophene units it was possible to further tune its photophysical and electrochemical properties. Additionally, the racemization barrier of these 3D PAHs was also modulated. All synthesized molecules were analyzed with regards to their optoelectronic properties and showed significantly lower optical bandgaps and much smaller half-lives for racemization in the range of a few microseconds in comparison to the parent structure. The integrated thiophene moiety enables easy post-functionalization, which led to the development of a wide range of substituted monkey saddles. Moreover, the monkey saddles were also applied as platforms for larger structures such as oligomers and cages.